Caracterização bioativa e atividade antioxidante de frutos e subprodutos de acerola verde: influência de matrizes encapsulantes e dos parâmetros de processo - Guedes, Tamna Joanan Farias Lima (2018)
Acerola is a fruit recognized worldwide for being an excellent source of ascorbic acid. Several researches have presented their high potential for other important bioactive compounds, such as anthocyanins, flavonoids and carotenoids, which are associated to the possible control of diseases with promising effects on human health. The green acerola residue has phenolic compound contents that were not fully extracted during the process. There is a growing trend towards the use and addition of value to such waste. However, the use of these natural substances ends up being limited, since much of the constituents responsible for the biological properties is highly unstable. Thus, the objectives of this work were: to characterize, extract and microencapsulate different extracts of green acerola residue obtained from the juice production process using different encapsulants and temperatures, to evaluate the effect of the drying process by spray drying on the different process parameters, morphology and bioactive compounds of the microparticles obtained. In order to reach these objectives, physical and chemical analyzes were performed on the different in natura and dehydrated residues, subsequently to obtain the liquid extracts, were then evaluated by the methods (ultrasound and maceration) and varying different concentrations of ethanol. With the determination of the best extraction, the encapsulation was carried out by spray dryer atomization, using maltodextrin, gum arabic and the combination of maltodextrin and gum arabic (1: 1) as encapsulating agents, being submitted to different drying air inlet temperatures (140 ° C and 160 ° C). In order to evaluate the microparticles, characterization analyzes (moisture, water activity, yield, encapsulation efficiency, solubility, hygroscopicity, density) morphology (SEM and particle size) were carried out, as well as the evaluation of phenolic, flavonoid and antioxidant activity by different methods. According to the results, the residues presented high contents of total phenolics, flavonoids and antioxidant activity, and the residue had the highest values. As for the different tests performed to optimize the encapsulation process, the use of maltodextrin and its combination with gum arabic, submitted to a temperature of 140 ° C, presented microparticles with good characteristics, with spherical shapes and smooth surfaces for the different extracts of agroindustrial residue of the green acerola. These data demonstrate the effective contribution of this research to the processes of obtaining powders of the various agroindustrial residues obtained from the production of concentrated juice of green acerola with functional properties associated to the different bioactive compounds.